The Law On Human Trafficking For The Purpose Of Illegal Organ Trade - Hasudungan Sinaga (International Journal of Social Service and Research, 2023)
The merits and drawbacks of organ sales are vigorously debated in Indonesia. Nevertheless, some argue that the trade in human organs should be prohibited, a stance supported by Indonesian law. Both organ recipients and donors bear significant responsibility in organ trade, as financial gain serves as the primary motive for organ brokers and medical professionals alike. This research aims to conduct a Legal Analysis of Human Trafficking for the Purpose of Organ Illegal Trade. The methodology employed is a literature review through online searches on various journal platforms such as Google Scholar, Science Direct, and the Garuda Portal, focusing on national and international scientific journal articles. The search, limited to the last four years (2019-2023), employed subject-specific terms like "human organ trafficking," "person trafficking," or "positive law." The search excluded articles containing only conceptual discussions. The findings reveal that the buying and selling of organs are ethically reprehensible and illegal in the healthcare industry, as outlined in Health Law Number 36 of 2009. Although ethical kidney transplants using organs obtained through sales are impossible, specific considerations should be noted. The purchase and sale of human organs and/or biological tissue constitute a specialized crime, with Article 192 of Law Number 36 of 2009 specifying criminal punishments. Those found deliberately engaging in organ or body tissue trade, as defined in Article 64 paragraph (3), may face a maximum sentence of 10 years in prison and a fine of IDR 1,000,000,000 (one billion rupiah).